THE POETICS OF ARCHITECTURE IN PROLETARIAT STATE: LAYING THE IDEOLOGY IN BRICKS (1918-1953) (Glocalism: Journal of Culture, Politics and Innovation, 2025)
Following the October Revolution and a brief period of civil unrest, Soviet leaders, architects, and engineers initiated a comprehensive reconstruction of the architectural landscape to sever ties with capitalism and align it with socialist-communist ideology. The ideology needed to be imbued within the architecture and built spaces. The paper explores the intricate relationship between architecture and ideology within the context of Soviet architecture from 1917 to 1953, a period characterized by significant socio-political transformations after the Bolshevik Revolution. Using a framework that integrates architectural semiotics and critical theory, the study examines how architectural forms and functions not only reflect but also propagate ideological narratives. To this end, official documents, archival materials, historical maps and photographs from the Soviet era on urban planning and design have been analysed. Additionally, Lenin’s theory of reflection, and Stalin’s socialist realism form the part of critical analysis for the study revealing the profound influence they project on architectural practices. As a method of study, one representative architecture has been selected from each of the three most prominent building types viz. “communal housing”, “workers’ clubs”, and “Stalin skyscrapers” to illustrate how these structures embody socialist principles and contribute to the construction of a new Soviet identity. Thus, the study underscores architecture’s role as a powerful tool for ideological dissemination, shaping social values and collective memory while serving as a medium for both power and resistance in the evolving landscape of Soviet society.
Keywords: architecture and ideology; Soviet architecture; art and propaganda; workers’ club; Stalin skyscrapers